2016
DOI: 10.1007/s00520-015-3070-5
|View full text |Cite
|
Sign up to set email alerts
|

Helplessness/hopelessness, minimization and optimism predict survival in women with invasive ovarian cancer: a role for targeted support during initial treatment decision-making?

Abstract: Objectives: Women with advanced ovarian cancer generally have a poor prognosis but there is significant variability in survival despite similar disease characteristics and treatment regimens. The aim of this study was to determine whether psychosocial factors predict survival in women with ovarian cancer, controlling for potential confounders. Methods:The sample comprised 798 women with invasive ovarian cancer recruited into the Australian Ovarian Cancer Study and a subsequent Quality of Life study. Validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Another strength of our study is the inclusion of dynamic changes in emotional assessment because people's emotions will probably change throughout the cancer trajectory, as supported by the literature . Thus, the use of baseline or cross‐sectional assessment of emotional variables may present a flaw in the study design.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength of our study is the inclusion of dynamic changes in emotional assessment because people's emotions will probably change throughout the cancer trajectory, as supported by the literature . Thus, the use of baseline or cross‐sectional assessment of emotional variables may present a flaw in the study design.…”
Section: Discussionmentioning
confidence: 99%
“…Marital status likely impacts survival through social support, although other beneficial consequences of marriage, such as an increase in financial resources and assistance in attending physician visits and receipt of cancer treatment, may also contribute. The role of social support in outcomes of ovarian cancer patients has been some-what mixed [40][41][42], although higher levels of emotional support or social attachment have been linked to better survival [41]. Additionally, studies have shown that in ovarian cancer patients, social support was associated with key biological pathways that have implications for outcomes, including the circulating and intratumoral immune response [43,44] as well as the stress response through an increase in tumor norepinephrine levels [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the PP intervention would result in greater improvement in hopelessness at 6 weeks (primary time point) and 12 weeks, given that this intervention targeted optimism/hope and other positive psychological constructs, and that these constructs have been prospectively associated with lower hopelessness, fewer suicidal thoughts and reduced suicidal behaviors (Hirsch & Conner, 2006; Hirsch et al 2007 a , b ; O'Connor et al 2008; Price et al 2016). Additionally, we expected that PP would be associated with greater improvements in suicidal ideation, depression, and positive psychological constructs at 6 and 12 weeks compared with the CF intervention.…”
Section: Introductionmentioning
confidence: 99%